Evaluation of a Simulation-Based Training Program on Childhood Trauma with Occupational Therapy Students - Julie Miller-Cribbs; Jedediah E. Bragg; Mary Isaacson; Eden D.E. Nay; Daniel Howell; Kristin Rodriguez; Frances Wen; Martina Jelley; Kim Coon (Journal of Occupational Therapy Education, 2021)
An educational and simulation-based training model, the Professional ACEs-Informed Training for Health Professionals designed for allied health students was evaluated using a pre-and-post design. The training model emphasizes trauma-informed care and uses social simulation to educate and train students with skills to address adverse childhood experiences. This study evaluated occupational therapy students’ (N=70) levels of self-efficacy and knowledge of trauma-informed care at both pre- and post-training. Analysis of variance results indicated a statistically significant improvement in students’ levels of general self-efficacy and knowledge from pre- to post-assessment (p < .01). These results are suggestive of the usefulness of brief didactics combined with simulation to educate occupational therapy students on adverse childhood experiences and trauma-informed care.